1998
DOI: 10.4319/lo.1998.43.1.0010
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of dissolved methane and methane oxidation in dimictic Lake Nojiri during winter

Abstract: Changes in the vertical distribution of dissolved CH, were monitored during the autumnal lake overturn period in mesotrophic Lake Nojiri, Japan (4.4 km* in area and 9.4 X 10' m3 in vol). A survey in 1992 revealed that the surface CH, concentration was highest in December, when the lake overturned. During the following two winters (1993-1994 and 1994-1995) we carried out detailed sampling during the autumnal overturn period. As a result of lake overturn in mid-December, CH, that had accumulated in the hypolimn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
85
3
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(100 citation statements)
references
References 20 publications
9
85
3
3
Order By: Relevance
“…Some other studies have also reported methane oxidation in lake water or sediments in the absence of O 2 , or at least at very low concentrations (1,35,42,54,62). Anaerobic oxidation of methane coupled to reduction of sulfate is well-known from various marine sediments (6,19,55) and saline lakes (29,31).…”
Section: Total Bacterial Abundancementioning
confidence: 99%
See 2 more Smart Citations
“…Some other studies have also reported methane oxidation in lake water or sediments in the absence of O 2 , or at least at very low concentrations (1,35,42,54,62). Anaerobic oxidation of methane coupled to reduction of sulfate is well-known from various marine sediments (6,19,55) and saline lakes (29,31).…”
Section: Total Bacterial Abundancementioning
confidence: 99%
“…Aerobic methane-oxidizing bacteria (MOB) in the water columns of lakes consume a significant part of the methane produced in the sediment or in anaerobic layers of water (46,54). Besides metabolizing methane that would otherwise be emitted to the atmosphere, they represent a route for reentry of carbon back into the food-webs (2,26,30,46).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, lakes emit roughly 8-48 Tg CH 4 year −1 , which is 6-16% of natural methane emissions and exceeds methane emissions from the ocean (Bastviken et al, 2004(Bastviken et al, , 2011Kirschke et al, 2013). In freshwater environments it has been estimated that anaerobic carbon mineralization contributes to 20-60% of total carbon mineralization rates (Boon and Mitchell, 1995;Hamilton et al, 1995;Utsumi et al, 1998), with methanogenesis making up 30-80% of this anaerobic activity (Kuivila et al, 1988;Bédard and Knowles, 1991). As such, it has been estimated that 20-59% of the OM delivered to sediments via suspended particles is converted to methane (Wetzel, 2001 and references therein).…”
Section: Methane Cycling In Inland Watersmentioning
confidence: 99%
“…In fact, for stratified lakes, methanotrophs can consume up to 90% of the dissolved CH 4 (Utsumi et al, 1998;Kankaala et al, 2006). However, in well-mixed estuaries, the activity of methanotrophs has been shown to be significantly less, allowing for the possible escape of CH 4 to the atmospshere (Abril et al, 2007).…”
Section: Introductionmentioning
confidence: 99%